Global terrestrial moisture recycling in Shared Socioeconomic Pathways - A. Staal; P. Meijer; P. Meijer; M. K. Nyasulu; M. K. Nyasulu; M. K. Nyasulu; O. A. Tuinenburg; S. C. Dekker (Earth System Dynamics)
Many areas across the globe rely for their precipitation supply on terrestrial precipitation recycling, which is the amount of precipitation that has evaporated from upwind land areas. Global warming and land-use changes may affect the future patterns of terrestrial precipitation recycling, but where and to which extent remains unclear. To study how the global patterns of precipitation recycling may change until the end of the 21st century, we present a new forward-tracking version of the three-dimensional atmospheric moisture-tracking model UTrack that is forced by output of the Norwegian Earth System Model (NorESM2). We simulate global precipitation recycling in four Shared Socioeconomic Pathways (SSPs) which are internally consistent combinations of climate and land-use scenarios used in the sixth phase of the Coupled Model Intercomparison Project. The scenarios range from mild to severe, namely SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5. We compare results for the middle of the century (2050–2059) and the end of the century (2090–2099) with a 2015–2024 baseline. We also calculate basin precipitation recycling for the 26 major river basins of the world. We find that the global terrestrial precipitation recycling ratio decreases with the severity of the SSPs and estimate a decrease in this ratio of 1.5 % with every degree of global warming. However, we find differences among regions and river basins in trends in precipitation recycling and whether projected drying or wetting is mainly contributed by land or ocean. Our results give critical insight into the relative contributions of global warming and land-use changes on global precipitation changes over the course of this century. In addition, our model paves the way for more detailed regional studies of future changes in terrestrial moisture recycling.